Slurry for electrolyte-resistant flame-retardant coating, electrolyte-resistant flame-retardant coating as well as preparation method and application of electrolyte-resistant flame-retardant coating

By using the use of phase -degraded polylefin flame retardant particles and phase transformer electrolytic flame retardant particles with electrolyte resistance coating in lithium -ion batteries, the problem of flammable and explosive batteries at high temperatures at high temperatures is solved, and the battery is achieved. Improvement of thermal stability and safety.

CN119350927AActive Publication Date: 2025-01-24STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3

Patent Information

Application Number
CN202411286992.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-24
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing lithium-ion batteries are flammable and explosive at high temperatures, resulting in safety accidents, and the thermal runaway problem of diaphragm and electrolyte is difficult to solve.

Method used

A kind of milizer for electrolytic flame retardant coating is used, which contains phase -changing polyolefin flame retardant particles and phase transformer electrolytic flame retardant particles. The flames are extinguished by the way of removing oxygen to remove oxygen through the halogen free radicals and dense smoke to delay the battery fire.

Benefits of technology

It effectively improves the thermal stability and flame retardant performance of lithium-ion batteries, delays the occurrence of battery fires, and improves battery safety without affecting the battery's electrical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350927A_ABST
    Figure CN119350927A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium batteries, and discloses slurry for an electrolyte-resistant flame-retardant coating, the electrolyte-resistant flame-retardant coating as well as a preparation method and application of the electrolyte-resistant flame-retardant coating. The slurry contains phase-change polyolefin flame-retardant particles, phase-change electrolyte flame-retardant particles, a stabilizing aid, a polymer binder and a first solvent, the average particle diameter of the phase-change polyolefin flame-retardant particles is 1-5 [mu] m; the average particle diameter of the phase change electrolyte flame-retardant particles is 0.4-3 [mu] m. When the electrolyte-resistant flame-retardant coating prepared from the slurry for the electrolyte-resistant flame-retardant coating provided by the invention is applied to a lithium ion battery, the capability of preventing the battery from catching fire due to overheating can be realized, so that the purpose of delaying a fire disaster of the battery is achieved, and the coating can interrupt the combustion of an organic electrolyte; when the electrolyte-resistant flame-retardant coating is applied to the lithium ion battery, the safety is greatly improved, the electrical property is not influenced, the national standard requirement is met, and the electrolyte-resistant flame-retardant coating is suitable for being applied to the field of electric energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a slurry for an electrolyte-resistant flame-retardant coating, an electrolyte-resistant flame-retardant coating, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are considered to be the mainstream energy storage devices that have a significant impact on modern society at various application scales, including portable power devices, electric vehicles, and stationary energy storage. However, if handled improperly, chemical energy can be suddenly released in the form of fire or explosion, leading to devastating accidents, especially involving electric vehicles and energy storage stations. Lithium battery safety accidents that have occurred in recent years continue to remind us that safety is a prerequisite for batteries, and battery safety issues need to be addressed before high-energy battery systems can be applied in the future. Although external physical safety devices such as pressure relief vents, positive temperature coefficient resistors, and battery management systems have been designed to protect battery modules, fire and explosion accidents have not been eliminated. The ultimate solution is to develop intrinsically safe battery components at the material level. The diaphragm and electrolyte are the root cause of battery fires and are the key to battery safety.

[0003] During the thermal runaway process, the diaphragm and liquid electrolyte play an important role. The diaphragm can isolate the positive and negative electrodes and prevent the chemical energy stored in the rechargeable battery from being converted into heat. However, most commercial diaphragms are composed of flammable and thermally unstable polyethylene (PE) or polypropylene (PP). When the internal temperature approaches its melting point, the diaphragm size shrinks, and the positive and negative electrodes come into direct contact, resulting in a battery short circuit. Short circuits caused by electrode contact are a common catalyst for thermal runaway. In this case, if the diaphragm can withstand higher temperatures without burning or shrinking, thermal runaway can be delayed or even stopped, thereby avoiding catastrophic events. Therefore, safe and reliable lithium-ion batteries require improved flame retardancy and thermal stability of the diaphragm.

[0004] Organic liquid electrolytes are highly flammable and serve as the "fuel" for battery combustion and explosion. Although non-flammable concentrated electrolytes have been developed, they are not effective in preventing thermal runaway of the battery caused by the redox reaction between the positive and negative electrodes. The development of flame-retardant separators can solve this serious problem to a certain extent. In addition, replacing flammable liquid electrolytes with solid-state electrolytes can solve the inherent problem of electrolyte flammability. Solid-state batteries also provide an attractive solution to safety issues, however, since solid-state batteries still require more research before they can be integrated into larger applications, it is very important to improve the thermal stability of current lithium-ion battery component designs. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of poor safety and thermal stability of lithium ion batteries in the prior art.

[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides a slurry for electrolyte resistant flame retardant coating, wherein the slurry contains phase change polyolefin flame retardant particles, phase change electrolyte flame retardant particles, a stabilizing aid, a polymer binder and a first solvent;

[0007] Wherein, based on the total weight of the slurry, the content of the phase change polyolefin flame retardant particles is 15-25wt%, the content of the phase change electrolyte flame retardant particles is 10-20wt%, the content of the stabilizing agent is 1.5-5.8wt%, the content of the polymer binder is 1-10wt%, and the content of the first solvent is 45-60wt%;

[0008] The phase-change polyolefin flame-retardant particles have an average particle diameter of 1-5 μm and a shell thickness of 0.01-0.9 μm;

[0009] The phase-change electrolyte flame-retardant particles have an average particle diameter of 0.4-3 μm and a shell thickness of 0.01-1 μm.

[0010] Preferably, the phase change polyolefin flame retardant particles are prepared by a method comprising the following steps:

[0011] In the presence of ethylene glycol dimethacrylate and polyethylene glycol octylphenyl ether, methyl methacrylate and flame retardant Ⅰ were ultrasonically treated to obtain an emulsion.

[0012] The emulsion is then contacted and mixed with an initiator.

[0013] Preferably, the flame retardant I is a combination of decabromodiphenylethane, aluminum hypophosphite, chlorinated polyethylene and antimony trioxide in a weight ratio of 2-5:1.5-4.5:0.8-2:1.

[0014] Preferably, the weight ratio of the methyl methacrylate, the ethylene glycol dimethacrylate, the polyethylene glycol octylphenyl ether, the flame retardant I and the initiator is 1: 0.08-0.12: 0.1-0.8: 0.8-1.2: 0.8-1.2.

[0015] Preferably, the phase-change electrolyte flame-retardant particles are prepared by a method comprising the following operations: stirring and mixing Fischer-Tropsch wax, flame retardant ⅠⅠ and silicon dioxide in the presence of a second solvent.

[0016] Preferably, the solid-liquid phase transition temperature of the Fischer-Tropsch wax is 80-100°C.

[0017] Preferably, the number average molecular weight of the Fischer-Tropsch wax is 1000-2000.

[0018] Preferably, the Fischer-Tropsch wax is an emulsion with a solid content of 33-50w%.

[0019] Preferably, the flame retardant II is a combination of tris(2,2,2-trifluoroethyl) phosphate and trimethyl phosphite in a weight ratio of 1-3:1.

[0020] Preferably, the amount of the second solvent used is 40-60 mL relative to 1 g of the silicon dioxide.

[0021] Preferably, the weight ratio of the Fischer-Tropsch wax, the flame retardant ⅠⅠ and the silicon dioxide is 5-15:4-6:1.

[0022] The second aspect of the present invention provides a method for preparing an electrolyte resistant flame retardant coating, the method comprising: mixing the components in the slurry for the electrolyte resistant flame retardant coating described in the first aspect.

[0023] The third aspect of the present invention provides an electrolyte resistant flame retardant coating prepared by the method described in the second aspect.

[0024] The fourth aspect of the present invention provides application of the electrolyte resistant flame retardant coating described in the third aspect in a lithium ion battery.

[0025] Compared with the prior art, the present invention has at least the following advantages:

[0026] (1) The electrolyte resistant flame retardant coating slurry provided by the present invention has a halogen free radical scavenging mechanism. The dense smoke generated by the reaction can be combined with the flame extinguishing mechanism by eliminating oxygen, thereby preventing the battery from overheating and catching fire, thereby delaying the battery fire.

[0027] (2) The electrolyte resistant flame retardant coating prepared by the slurry for electrolyte resistant flame retardant coating provided by the present invention can generate free radicals with flame retardant properties at high temperatures. The free radicals can capture flammable free radicals such as hydrogen and oxygen in the gas phase, thereby preventing these free radicals from undergoing a chain reaction and interrupting the combustion of the organic electrolyte.

[0028] (3) When the electrolyte-resistant flame-retardant coating provided by the present invention is used as a diaphragm safety coating to make a safe composite diaphragm, the shell of the phase change flame-retardant particles in the coating undergoes phase change and melts into a molten state at high temperatures. At the same time, the electrolyte-resistant flame-retardant coating can prevent the polyolefin material diaphragm from burning. In addition, the diaphragm's own temperature-resistant functional coating also ensures its thermal stability.

[0029] (4) When the electrolyte-resistant flame-retardant coating provided by the present invention is applied as a safety coating on a diaphragm and an electrode sheet to respectively form a safe composite diaphragm, a safe positive electrode, and a safe negative electrode, and applied to a lithium-ion battery, in terms of the battery manufacturing process, the adhesion between the electrode sheet and the diaphragm makes the battery cell less likely to deform, and the production yield is high; in terms of battery operating performance, safety is comprehensively improved without affecting the battery electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a schematic diagram of the battery cell structure in Application Example 1 of the present invention;

[0031] Figure 2 Graph showing the discharge capacities of the lithium-ion batteries of Application Example 1 of the present invention and Comparative Application Example 1 at different rates.

[0032] Description of Reference Numerals

[0033] 1. Safety composite diaphragm

[0034] 2. Safe positive electrode

[0035] 3. Safe negative electrode

[0036] 4. Phase change polyolefin flame retardant particles

[0037] 5. Phase change electrolyte flame retardant particles DETAILED DESCRIPTION

[0038] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0039] As mentioned above, the first aspect of the present invention provides a slurry for electrolyte resistant flame retardant coating, the slurry contains phase change polyolefin flame retardant particles, phase change electrolyte flame retardant particles, a stabilizing aid, a polymer binder and a first solvent;

[0040] Wherein, based on the total weight of the slurry, the content of the phase change polyolefin flame retardant particles is 15-25wt%, the content of the phase change electrolyte flame retardant particles is 10-20wt%, the content of the stabilizing agent is 1.5-5.8wt%, the content of the polymer binder is 1-10wt%, and the content of the first solvent is 45-60wt%;

[0041] The average particle diameter of the phase-change polyolefin flame-retardant particles is 1-5 μm;

[0042] The phase-change electrolyte flame-retardant particles have an average particle diameter of 0.4-3 μm.

[0043] The inventor of the present invention found in the research process that the electrolyte-resistant flame-retardant coating can be prepared by compounding a slurry containing phase-change polyolefin flame-retardant particles, phase-change electrolyte flame-retardant particles, a stabilizing aid, a polymer binder and a first solvent. When the electrolyte-resistant flame-retardant coating is at high temperature, the phase-change flame-retardant particles undergo phase change to absorb part of the heat, delaying the temperature rise of the battery core, and at the same time, the phase-change polyolefin flame-retardant particles release the internal flame retardant, and utilize the synergistic effect of the two flame-retardant mechanisms, namely the halogen free radical scavenging mechanism, combined with the dense smoke generated by the reaction, to extinguish the flame by excluding oxygen, thereby achieving the ability to prevent the battery from overheating and catching fire, so as to delay the battery fire. In addition, the phase-change electrolyte flame-retardant particles release the core compound electrolyte flame retardant, which can produce free radicals with flame-retardant properties at high temperatures. The free radicals can capture flammable free radicals such as hydrogen and oxygen in the gas phase, thereby preventing these free radicals from chain reaction and interrupting the combustion of the organic electrolyte.

[0044] The inventors further discovered that when the electrolyte-resistant flame-retardant coating is used as a diaphragm safety coating, the outer shell of the phase change flame-retardant particles in the coating can phase change and melt into a molten state at high temperatures, while utilizing the synergistic flame-retardant mechanism of the core flame-retardant material inside the phase change polyolefin flame-retardant particles to prevent the polyolefin material diaphragm from burning; in addition, the diaphragm's own temperature-resistant functional coating can also ensure its thermal stability.

[0045] The inventors continued their research and found that when the electrolyte-resistant flame-retardant coating is used as a coating on the edge of the electrode, the coating not only does not affect the electrical properties of the electrode, but the polymer binder in the coating can make the electrode and the diaphragm bond better, the battery cell is not easy to deform during trial production and operation, and the production yield is high; and the phase change flame-retardant particles in the coating can prevent the positive and negative electrodes of the battery cell from short-circuiting at high temperatures, and at high temperatures, the synergistic flame-retardant mechanism of the coating is used to ensure safety.

[0046] Preferably, the phase-change polyolefin flame-retardant particles are of a core-shell structure.

[0047] Preferably, the phase change polyolefin flame retardant particles are prepared by a method comprising the following steps:

[0048] In the presence of ethylene glycol dimethacrylate and polyethylene glycol octylphenyl ether, methyl methacrylate and flame retardant Ⅰ were ultrasonically treated to obtain an emulsion.

[0049] The emulsion is then contacted and mixed with an initiator.

[0050] According to a particularly preferred embodiment, the phase change polyolefin flame retardant particles are also prepared by a method comprising the following steps:

[0051] S1: In the presence of ethylene glycol dimethacrylate and polyethylene glycol octylphenyl ether, methyl methacrylate and flame retardant I are stirred at a rotation speed of 10000-15000 rpm for 15-40 minutes, and ultrasonically treated to obtain an emulsion;

[0052] S2: dispersing the initiator with methanol to obtain an intermediate;

[0053] S3: then contacting and mixing the emulsion with the intermediate;

[0054] S4: washing, drying and sieving the product obtained by the contact mixing in sequence; the sieving is to sifte through a 2500-12500 mesh Chinese standard sieve and take the sieve residue.

[0055] Preferably, in the intermediate, the concentration of the initiator is 0.01-0.03 g / mL.

[0056] Preferably, the flame retardant I is selected from a basic flame retardant and / or a flame retardant synergist. More preferably, the basic flame retardant is selected from at least two of decabromodiphenylethane, microencapsulated red phosphorus, melamine polyphosphate, bromocyclododecane, aluminum hypophosphite, octabromoether, tris(2,3-dibromopropyl)isocyanurate, and ammonium polyphosphate; and the flame retardant synergist is selected from at least one of chlorinated polyethylene, 3.5-hydrate zinc borate, and antimony trioxide.

[0057] Further preferably, the flame retardant I is a combination of decabromodiphenylethane, aluminum hypophosphite, chlorinated polyethylene and antimony trioxide in a weight ratio of 2-5:1.5-4.5:0.8-2:1. In this preferred case, the technical solution provided by the present invention can obtain a lithium-ion battery with higher safety.

[0058] Preferably, in step S1, in the flame retardant I, the chlorine content of the chlorinated polyethylene is 35-73 wt%.

[0059] Preferably, in step S1, the conditions of the ultrasonic treatment include: a power ratio of 30-70% and a time of 20-40 min.

[0060] Preferably, in step S2, the initiator is 2,2'-azo-bis-(2,4-dimethylvaleronitrile).

[0061] Preferably, the weight ratio of the methyl methacrylate, the ethylene glycol dimethacrylate, the polyethylene glycol octylphenyl ether, the flame retardant I and the initiator is 1: 0.08-0.12: 0.1-0.8: 0.8-1.2: 0.8-1.2. In this preferred case, the technical solution provided by the present invention can obtain a lithium-ion battery with higher safety.

[0062] Preferably, in step S3, the contact mixing conditions include: a rotation speed of 800-1700 rpm, a temperature of 25-70° C., and a time of 290-480 min.

[0063] More preferably, in step S3, the contact mixing includes a first contact mixing and a second contact mixing performed sequentially, wherein the conditions of the first contact mixing include: a rotation speed of 1200-1700 rpm, a temperature of 25-30°C, and a time of 10-30 min; the conditions of the second contact mixing include: a rotation speed of 800-1500 rpm, a temperature of 50-70°C, and a time of 280-450 min.

[0064] In step S4, the present invention has no particular restrictions on the solvent used for the cleaning and the drying time. For example, deionized water and ethanol can be used for cleaning 1-5 times respectively, and the drying time is 24 hours.

[0065] Preferably, the phase-change electrolyte flame-retardant particles are prepared by a method comprising the following operations: stirring and mixing the thermosensitive sealing agent, the flame retardant ⅠⅠ and the hollow porous oxide in the presence of a second solvent.

[0066] Preferably, the thermosensitive sealing agent is selected from at least one of plant wax, microcrystalline wax, polyethylene glycol and fatty acid, and the hollow porous oxide is selected from at least one of ferrosoferric oxide, cerium oxide, manganese dioxide, aluminum oxide, titanium dioxide and magnesium oxide.

[0067] According to a preferred embodiment, the phase-change electrolyte flame-retardant particles are prepared by a method comprising the following operations: stirring and mixing Fischer-Tropsch wax, flame retardant ⅠⅠ and silicon dioxide in the presence of a second solvent.

[0068] Preferably, the stirring and mixing conditions include: temperature of 40-60° C. and time of 60-100 min.

[0069] According to a particularly preferred embodiment, in the presence of a second solvent, Fischer-Tropsch wax and flame retardant ⅠⅠ are first stirred and mixed, and then silicon dioxide is added to the obtained mixture for a second stirring and mixing, and the product obtained by the second stirring and mixing is sequentially washed, dried and sieved; the sieving is performed by sieving with a sieve of Chinese standard of 5000-12500 mesh and taking the sieve.

[0070] Further preferably, the first stirring and mixing conditions include: temperature of 40-60°C, time of 10-30 min; the second stirring and mixing conditions include: temperature of 50-60°C, time of 50-70 min.

[0071] The present invention has no particular restrictions on the solvent used for the cleaning Ⅱ and the time for the drying Ⅱ. For example, deionized water and ethanol can be used for cleaning 1-5 times respectively, and the drying Ⅱ time is 0.5h.

[0072] Preferably, the solid-liquid phase transition temperature of the Fischer-Tropsch wax is 80-100°C.

[0073] Preferably, the number average molecular weight of the Fischer-Tropsch wax is 1000-2000.

[0074] Preferably, the Fischer-Tropsch wax is an emulsion with a solid content of 33-50w%.

[0075] Preferably, the flame retardant II is a combination of tris(2,2,2-trifluoroethyl) phosphate and trimethyl phosphite in a weight ratio of 1-3:1. In this preferred embodiment, the technical solution provided by the present invention can obtain a lithium-ion battery with higher safety.

[0076] Preferably, the silicon dioxide has a spherical hollow mesoporous structure, and the average particle diameter is 0.4-3 μm.

[0077] Preferably, the second solvent is selected from at least one of hot ethanol, acetone, methanol, dichloromethane, toluene and ether, more preferably hot ethanol. The "hot ethanol" refers to ethanol after heating.

[0078] Preferably, the amount of the second solvent used is 40-60 mL relative to 1 g of the silicon dioxide.

[0079] Preferably, the weight ratio of the Fischer-Tropsch wax, the flame retardant ⅠⅠ and the silicon dioxide is 5-15:4-6:1. In this preferred embodiment, the technical solution provided by the present invention can obtain a lithium-ion battery with higher safety.

[0080] Preferably, the stabilizing aid is selected from at least two of a dispersant, a wetting agent, and a thickener.

[0081] Preferably, the dispersant is selected from at least one of acrylic polymers, amine-containing polyacrylates, acrylic polymer block copolymers, polyacrylates, fatty acid polyethylene glycol esters, sodium polyacrylate and copolymers containing acidic groups, more preferably acrylic polymers and / or amine-containing polyacrylates.

[0082] The present invention has no special requirements on the specific types of the acrylic polymer and the amino-containing polyacrylate. The following text of the present invention provides specific types of acrylic polymers and amino-containing polyacrylates by way of example, which should not be construed as a limitation of the present invention by those skilled in the art.

[0083] Preferably, the acrylic acid high molecular polymer is a yellow liquid with a solid content of 30-42 wt%.

[0084] Preferably, the wetting agent is selected from at least one of sodium succinate, sodium alkyl sulfonate and sodium butylnaphthalene sulfonate, more preferably sodium succinate.

[0085] Preferably, the thickener is selected from sodium carboxymethyl cellulose, methyl hydroxymethyl cellulose and / or bentonite, more preferably sodium carboxymethyl cellulose.

[0086] Preferably, the polymer binder is selected from at least one of polyvinylidene fluoride, styrene butadiene rubber and polyacrylic acid, more preferably polyvinylidene fluoride and / or styrene butadiene rubber.

[0087] Preferably, the styrene-butadiene rubber is an emulsion with a solid content of 40-50 wt%.

[0088] Preferably, the first solvent is selected from at least one of deionized water, N-methylpyrrolidone, N,N-dimethylformamide, acetone and tetrahydrofuran, more preferably deionized water and / or N-methylpyrrolidone.

[0089] As mentioned above, the second aspect of the present invention provides a method for preparing an electrolyte resistant flame retardant coating, the method comprising: mixing the components in the slurry for the electrolyte resistant flame retardant coating described in the first aspect.

[0090] The slurry for electrolyte resistant flame retardant coating is the same as or similar to the slurry for electrolyte resistant flame retardant coating described in the first aspect of the present invention, and will not be described in detail herein.

[0091] As mentioned above, the third aspect of the present invention provides an electrolyte resistant flame retardant coating prepared by the method described in the second aspect.

[0092] Preferably, the viscosity of the electrolyte-resistant flame-retardant coating at 25° C. is 60-2500 mPa.S.

[0093] As mentioned above, the fourth aspect of the present invention provides the use of the electrolyte resistant flame retardant coating described in the third aspect in a lithium ion battery.

[0094] Preferably, the application includes a functional separator, a positive electrode sheet and a negative electrode sheet.

[0095] Preferably, when the electrolyte-resistant flame-retardant coating is applied to a functional diaphragm, the electrolyte-resistant flame-retardant coating is applied to the uncoated smooth surface of the functional diaphragm by means of a micro-concave roller, spot coating or spraying, and then dried to obtain a safe composite diaphragm with the electrolyte-resistant flame-retardant coating.

[0096] More preferably, the coating conditions include: a thickness of 2-5 μm, preferably 3 μm; a speed of 3-6 m / min; and a drying temperature of 35-55°C.

[0097] Further preferably, the functional diaphragm is a mixed coating diaphragm of aluminum oxide and polyvinylidene fluoride, with a thickness of 8-17 μm.

[0098] Preferably, when the electrolyte-resistant flame-retardant coating is applied to the positive electrode plate, the electrolyte-resistant flame-retardant coating is spot-coated on the positive and negative pole ears and the boundary of the material area of ​​the carbon-coated aluminum foil, and dried to obtain a safe positive electrode with the electrolyte-resistant flame-retardant coating.

[0099] More preferably, the conditions for the spot coating include: a width of 3-6 mm, a single-side thickness of 30-50 μm, a speed of 15-20 m / min; and a drying temperature of 130-150°C.

[0100] Further preferably, the thickness of the carbon-coated aluminum foil is 12-18 μm, and the thickness of the double-sided carbon-coated layer in the carbon-coated aluminum foil is 1-3 μm.

[0101] Preferably, when the electrolyte-resistant flame-retardant coating is applied to the negative electrode plate, the electrolyte-resistant flame-retardant coating is synchronously spot-coated on the boundary between the double-sided pole ears and the material area of ​​the copper foil during the electrode coating process, and dried to obtain a safe negative electrode with the electrolyte-resistant flame-retardant coating.

[0102] More preferably, the conditions for the spot coating include: a width of 3-7 mm, a thickness of 20-40 μm, a speed of 12-18 m / min; and a drying temperature of 95-120°C.

[0103] Further preferably, the copper foil has a thickness of 4.5-9 μm.

[0104] The present invention will be described in detail below through examples.

[0105] In the following examples, unless otherwise specified, the raw materials and equipment used are all commercially available, and the solvents used are all analytically pure.

[0106] Phase change polyolefin flame retardant particles:

[0107] Ethylene glycol dimethacrylate was purchased from Sinopharm Chemical Reagent Co., Ltd. with the brand number XW00979051.

[0108] Polyethylene glycol octylphenyl ether was purchased from Sinopharm Chemical Reagent Co., Ltd., brand number 30188928.

[0109] Chlorinated polyethylene, purchased from Sinopharm Chemical Reagent Co., Ltd., brand number XW6323166301; chlorine content is 35wt%.

[0110] Phase change electrolyte flame retardant particles:

[0111] Fischer-Tropsch wax, emulsion, solid content of 33.5%, number average molecular weight of 1000, customized by Shanghai Xinnuo Chemical Co., Ltd.; solid-liquid phase transition temperature of 90°C.

[0112] Silica, customized by Xi'an Qiyue Biotechnology Co., Ltd.

[0113] Slurry for electrolyte resistant flame retardant coating:

[0114] Acrylic acid polymer, yellow liquid, solid content 40±2%, purchased from Shanghai Yingcheng Chemical Co., Ltd., brand DP 21.

[0115] Acrylic acid high molecular block copolymer was purchased from Guangzhou Houhuan Chemical Additive Co., Ltd., brand HH2021.

[0116] The amine-containing polyacrylate was purchased from Guangzhou Houhuan Chemical Additive Co., Ltd. with the brand name HH2016D.

[0117] Polyvinylidene fluoride was purchased from Changsha Xinxing New Energy Technology Co., Ltd. with the brand name JHD-1015.

[0118] Styrene butadiene rubber, emulsion, solid content 40 wt%, purchased from Wuxi Sigma New Energy Technology Co., Ltd., brand A-100.

[0119] In the following examples and comparative examples, the relevant characteristic parameters were measured by the following methods:

[0120] (1) Air permeability: measured using a Gurley air permeability meter according to the method specified in 6.5.4 of GB / T36363-2018.

[0121] (2) Oxygen index: The limiting oxygen index (LOI value) of the safety composite diaphragm is tested using a limiting oxygen index instrument to evaluate the flammability of the safety composite diaphragm. The test method is: the sample is fixed vertically in a transparent combustion tube through which a fixed ratio of nitrogen and oxygen mixed gas flows continuously. The minimum oxygen concentration (volume fraction) when the burning time is greater than 180 seconds or the burning distance exceeds 50 mm is the measured limiting oxygen index (LOI) value.

[0122] (3) Electrochemical stability: Linear sweep voltammetry (LSV) test was carried out using CHI660e electrochemical workstation to evaluate the electrochemical stability of the safety composite diaphragm in electrolyte.

[0123] (4) Overcharge test: The test is conducted in accordance with the method specified in Appendix A Test Method A.2.12 of GB / T 36276-2018, and the lithium-ion battery is clamped in a stainless steel clamp to observe whether the lithium-ion battery opens, overflows, emits smoke, or catches fire or explodes.

[0124] (5) Short-circuit test: Refer to the method specified in Appendix A Test Method A.2.14 of GB / T 36276-2018 to test whether the lithium-ion battery opens, overflows, smokes, catches fire or explodes.

[0125] (6) Heating test: Test according to the method specified in Appendix A Test method A.2.18 of GB / T 36276-2018.

[0126] (7) Thermal runaway test: The test shall be conducted in accordance with the method specified in Appendix A Test Method A.2.19 of GB / T 36276-2018.

[0127] (8) Needle puncture test: The battery cell is placed in a needle puncture test machine for needle puncture test. The test condition is a 6mm steel needle. The lithium-ion battery is observed to see if it opens, overflows, smokes, catches fire or explodes.

[0128] (9) Electrical performance test: Refer to the method specified in Appendix A Test Method A.2.5 of GB / T 36276-2018 to obtain data and draw a discharge capacity diagram.

[0129] In the following examples, the amount of methyl methacrylate used is 5.64 g, and the amount of Fischer-Tropsch wax used is 4 g; each 1 wt % represents 1 g.

[0130] Preparation Example 1-1: Preparation of phase-change polyolefin flame-retardant particles

[0131] (1) In the presence of ethylene glycol dimethacrylate and polyethylene glycol octylphenyl ether, methyl methacrylate and flame retardant I (decabromodiphenylethane, chlorinated polyethylene and antimony trioxide) were added to deionized water, stirred at a speed of 13000 rpm for 30 minutes, and subjected to ultrasonic treatment to obtain a uniform emulsion;

[0132] (2) dispersing an initiator (2,2'-azo-bis-(2,4-dimethylvaleronitrile)) with methanol to obtain an intermediate (in the intermediate, the concentration of the initiator is 0.01 g / mL);

[0133] (3) then contacting and mixing the emulsion with the intermediate (conducting a first contact mixing and a second contact mixing in sequence) until the reaction is completed;

[0134] (4) The product obtained by the contact mixing is washed twice with deionized water and ethanol to remove the surfactant, and is dried at room temperature for 24 hours. Finally, the product is sieved (using a 12500 mesh Chinese standard sieve to sieve the sieve) to obtain phase change polyolefin flame retardant particles.

[0135] The methods for preparing phase change polyolefin flame retardant particles used in the examples of the present invention are the same, except that the raw material ratios and reaction conditions are different, and different phase change polyolefin flame retardant particles are obtained respectively. The raw material ratios and reaction conditions of the phase change polyolefin flame retardant particles are listed in Table 1, and the unlisted parts are the same as those in Preparation Example 1-1.

[0136] Table 1

[0137]

[0138] Preparation Example 2-1: Preparation of phase change electrolyte flame retardant particles

[0139] (1) In the presence of a second solvent (hot ethanol), Fischer-Tropsch wax and flame retardant ⅠⅠ (tris(2,2,2-trifluoroethyl) phosphate and trimethyl phosphite) are first stirred and mixed, and then silicon dioxide is added to the obtained mixed solution to perform a second stirring and mixing;

[0140] (2) The product obtained by the second stirring and mixing was placed in a vacuum environment at 50° C. and dried for 0.5 h, then centrifuged and washed twice with ethanol, dried at room temperature and sieved (using a 5000-mesh Chinese standard sieve to sieve the sieve) to obtain phase change electrolyte flame retardant particles.

[0141] The methods for preparing phase change electrolyte flame retardant particles used in the examples of the present invention are the same, except that the raw material ratios and reaction conditions are different, and different phase change electrolyte flame retardant particles are obtained respectively. The raw material ratios and reaction conditions of the phase change electrolyte flame retardant particles are listed in Table 2, and the unlisted parts are the same as those in Preparation Example 2-1.

[0142] Table 2

[0143]

[0144] The following examples are used to illustrate a method for preparing an electrolyte resistant flame retardant coating provided by the present invention. Example 1

[0145] First, stabilizers (sodium succinate, sodium carboxymethyl cellulose) are added to the first solvent (first deionized water) in sequence, and stirred at a speed of 500 rpm until they are evenly mixed; acrylic polymer and phase change polyolefin flame retardant particles are added, and stirred at a speed of 800 rpm until they are evenly dispersed; the first solvent (second deionized water), acrylic polymer block copolymer, and phase change electrolyte flame retardant particles are added, and stirred at a speed of 1000 rpm until they are evenly dispersed; finally, a polymer binder (styrene-butadiene rubber) is added, and stirred at a speed of 500 rpm until they are evenly dispersed to obtain an electrolyte-resistant flame retardant coating.

[0146] The methods for preparing electrolyte-resistant flame-retardant coatings used in the examples of the present invention are the same, except that the types, contents and characteristic parameters of raw materials are different, and different electrolyte-resistant flame-retardant coatings are obtained respectively. The types, contents and characteristic parameters of raw materials for the electrolyte-resistant flame-retardant coatings are listed in Table 3, and the unlisted parts are the same as in Example 1.

[0147] Table 3

[0148]

[0149] Table 3 (continued)

[0150]

[0151] Application Example 1

[0152] (1) The electrolyte-resistant flame-retardant coating prepared in Example 1 is applied to the uncoated smooth surface of the functional diaphragm (a mixed coating diaphragm of aluminum oxide and polyvinylidene fluoride) by means of a micro-concave roller, and then dried and rolled to obtain a safety composite diaphragm A1 with an electrolyte-resistant flame-retardant coating;

[0153] The coating conditions are as follows: thickness of 3 μm, speed of 5 m / min; drying temperature of 45° C.; and the functional diaphragm is a single-sided coating with a thickness of 12 μm.

[0154] (2) The electrolyte-resistant flame-retardant coating prepared in Example 2 is spot-coated on the front and back tabs of the carbon-coated aluminum foil and the boundary between the material area, and dried to obtain a safe positive electrode B1 with the electrolyte-resistant flame-retardant coating;

[0155] Among them, the conditions for the above-mentioned spot coating are: width is 5mm, single-sided thickness is 40μm, and speed is 15m / min; the above-mentioned drying temperature is 145°C; the thickness of the above-mentioned carbon-coated aluminum foil is 13μm, and the thickness of the double-sided carbon-coated layer in the above-mentioned carbon-coated aluminum foil is 1μm.

[0156] (3) The electrolyte-resistant flame-retardant coating prepared in Example 3 is simultaneously spot-coated on the boundary between the electrode tabs on both sides of the copper foil and the material area during the electrode coating process, and then dried to obtain a safe negative electrode C1 with the electrolyte-resistant flame-retardant coating;

[0157] The conditions for the spot coating are: a width of 4 mm, a thickness of 30 μm, and a speed of 12 m / min; the drying temperature is 100° C.; and the thickness of the copper foil is 6 μm.

[0158] (4) The safety composite separator A1, the safety positive electrode B1 and the safety negative electrode C1 are prepared into a battery cell through a lamination process, wherein the electrolyte-resistant flame-retardant coating of the safety composite separator in each battery cell faces the safety positive electrode side. After assembly, high-temperature baking, liquid injection and chemical conversion, a lithium-ion battery Y1 is obtained.

[0159] Application Examples 2 to 7

[0160] According to the method of Application Example 1, except that in step (1), the electrolyte resistant flame retardant coating prepared in Example 1 is replaced by the electrolyte resistant flame retardant coatings prepared in Examples 2 to 7, respectively, and the rest are the same, to obtain safety composite diaphragms A2, A3, A4, A5, A6, and A7, respectively;

[0161] In step (4), the safety composite diaphragm A1 is replaced by safety composite diaphragms A2, A3, A4, A5, A6 and A7 respectively, and the rest are the same, to obtain lithium ion batteries Y2, Y3, Y4, Y5, Y6 and Y7 respectively.

[0162] Comparative Application Example 1 to Comparative Application Example 3

[0163] According to the method of Application Example 1, except that in step (1), the electrolyte resistant flame retardant coating prepared in Example 1 is replaced by the electrolyte resistant flame retardant coatings prepared in Comparative Examples 1 to 3 respectively, and the rest are the same, to obtain safety composite diaphragms DA1, DA2, and DA3 respectively;

[0164] In step (4), the safety composite diaphragm A1 is replaced by safety composite diaphragms DA1, DA2, and DA3 respectively, and the rest are the same, to obtain lithium-ion batteries DY1, DY2, and DY3 respectively.

[0165] Test Example 1

[0166] The aforementioned test methods were used to measure the performance of the safety composite diaphragms obtained in each example, including air permeability, oxygen index, and electrochemical stability. The test results are shown in Table 4.

[0167] Table 4

[0168] Air permeability s / 100cc Oxygen index% Electrochemical stability A1 188 42 Stablize A2 195 40 Stablize A3 201 39 Stablize A4 210 33 Stablize A5 230 31 Stablize A6 217 32 Stablize A7 245 31 Stablize DA1 310 26 Stablize DA2 301 28 Unstable DA3 297 27 Unstable

[0169] Test Example 2

[0170] The performance of the lithium-ion batteries obtained in each example was measured using the aforementioned test methods, including: overcharge test, short circuit test, heating test, thermal runaway test and electrical performance test. Then, the obtained lithium-ion batteries were subjected to a needle penetration test in accordance with the IEC62133 standard. The test results are shown in Table 5.

[0171] The present invention Figure 1 The schematic diagram of the battery cell structure prepared in Application Example 1 is provided as an example. Figure 1 It can be seen that the battery cell structure contains a safety composite diaphragm 1, a safety positive electrode 2, a safety negative electrode 3, phase change polyolefin flame retardant particles 4, and phase change electrolyte flame retardant particles 5, which means that the safety composite diaphragm, the safety positive electrode, and the safety negative electrode are loaded with phase change polyolefin flame retardant particles and phase change electrolyte flame retardant particles. When the battery fails, the above-mentioned functional ions release the internal flame retardant to ensure the safety of the battery.

[0172] The present invention Figure 2 The discharge capacity diagrams of the lithium ion batteries of Application Example 1 and Comparative Application Example 1 at different rates are provided as examples. Figure 2 It can be seen that the electrolyte resistant flame retardant coating prepared by the slurry for electrolyte resistant flame retardant coating provided by the present invention has excellent discharge capacity and rate performance when applied to lithium ion batteries.

[0173] Table 5

[0174]

[0175] It can be seen from the above results that the electrolyte resistant flame retardant coating prepared by the slurry for electrolyte resistant flame retardant coating provided by the present invention has strong thermal stability, which can not only prevent the battery from overheating and catching fire, thereby achieving the purpose of delaying battery fire, but also the coating can interrupt the combustion of organic electrolyte; when the electrolyte resistant flame retardant coating is applied to lithium-ion batteries, the safety is greatly improved, and the electrical performance is not affected and meets the national standards, and is suitable for application in the field of power energy storage.

[0176] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A slurry for electrolyte resistant flame retardant coating, characterized in that: The slurry contains phase-change polyolefin flame-retardant particles, phase-change electrolyte flame-retardant particles, a stabilizing aid, a polymer binder and a first solvent; Wherein, based on the total weight of the slurry, the content of the phase change polyolefin flame retardant particles is 15-25wt%, the content of the phase change electrolyte flame retardant particles is 10-20wt%, the content of the stabilizing agent is 1.5-5.8wt%, the content of the polymer binder is 1-10wt%, and the content of the first solvent is 45-60wt%; The average particle diameter of the phase-change polyolefin flame-retardant particles is 1-5 μm; The average particle diameter of the phase-change electrolyte flame-retardant particles is 0.4-3 μm.

2. The slurry according to claim 1, wherein The phase-change polyolefin flame-retardant particles are prepared by a method comprising the following steps: In the presence of ethylene glycol dimethacrylate and polyethylene glycol octylphenyl ether, methyl methacrylate and flame retardant Ⅰ were ultrasonically treated to obtain an emulsion. The emulsion is then contacted and mixed with an initiator.

3. The slurry according to claim 2, wherein The flame retardant I has a content weight ratio of 2-5: A combination of decabromodiphenylethane, aluminum hypophosphite, chlorinated polyethylene and antimony trioxide in a ratio of 1.5-4.5:0.8-2:

1.

4. The slurry according to claim 2, wherein The weight ratio of the methyl methacrylate, the ethylene glycol dimethacrylate, the polyethylene glycol octylphenyl ether, the flame retardant I and the initiator is 1: 0.08-0.12: 0.1-0.8: 0.8-1.2: 0.8-1.

2.

5. The slurry according to claim 1, wherein The phase-change electrolyte flame-retardant particles are prepared by a method comprising the following operations: stirring and mixing Fischer-Tropsch wax, flame retardant ⅠⅠ and silicon dioxide in the presence of a second solvent.

6. The slurry according to claim 5, wherein The solid-liquid phase transition temperature of the Fischer-Tropsch wax is 80-100°C; And / or, the flame retardant Ⅱ is a combination of tris(2,2,2-trifluoroethyl) phosphate and trimethyl phosphite in a weight ratio of 1-3:

1.

7. The slurry according to claim 5, wherein The amount of the second solvent is 40-60 mL relative to 1 g of the silicon dioxide; And / or, the weight ratio of the Fischer-Tropsch wax, the flame retardant ⅠⅠ and the silicon dioxide is 5-15:4-6:

1.

8. A method for preparing an electrolyte-resistant flame-retardant coating, characterized in that: The method comprises: mixing the components in the slurry for electrolyte resistant flame retardant coating according to any one of claims 1 to 7.

9. The electrolyte-resistant flame-retardant coating prepared by the method according to claim 8.

10. Use of the electrolyte-resistant flame-retardant coating according to claim 9 in lithium-ion batteries.

Citation Information

Patent Citations

  • flame retardant paints

    AT207487B

  • Preparation process of flame retardant battery

    CN104167567A

  • Flame-retardant lithium battery coating diaphragm, preparation method thereof and lithium ion battery

    CN116231228A

Cited By

  • High-efficiency closed-pore high-stability slurry, preparation method thereof, lithium ion battery and electric equipment

    CN121983749A